2016
DOI: 10.1080/21645515.2016.1219004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the contemporary Zika virus in immunocompetent mice

Abstract: Zika virus (ZIKV) has raised global public health concerns due to its rapid transmission and unexpected clinical manifestations. 1 No vaccine or antiviral treatment is currently available, and the development of animal model of ZIKV infection is of priority. 2,3 The mouse model of ZIKV infection was recently developed using A129 and AG129 mice. [4][5][6][7] However, both mice are deficient in critical innate immune signaling, and more importantly, these animals are limited resource, and are not available for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 10 publications
3
15
0
Order By: Relevance
“…5A). The highest viral load was observed in the testes, consistent with observations in other animal models (17,32). Then, we performed immunostaining of testis tissue with convalescence serum from a recovered ZIKV patient (33).…”
supporting
confidence: 84%
“…5A). The highest viral load was observed in the testes, consistent with observations in other animal models (17,32). Then, we performed immunostaining of testis tissue with convalescence serum from a recovered ZIKV patient (33).…”
supporting
confidence: 84%
“…As our in vitro data indicated that 25HC promoted anti-viral activity against ZIKV, we next tested the in vivo antiviral effects of 25HC in 3- to 4-week-old immunocompetent BALB/c mice as described previously (Larocca et al, 2016; Zhang et al, 2016). Animals were treated with 25HC (50 mg/kg) or vehicle and infected with ZIKV strain GZ01/2016 intraperitoneally (i.p.).…”
Section: Resultsmentioning
confidence: 99%
“…In the viremia model [39,40], temoporfin treatment resulted in about 100-fold reduction in ZIKV-induced viremia in immunocompetent Balb/C mice compared to the vehicle control ( Figure 5A). In the lethal A129 mouse model [41,42], all the ZIKV-infected animals treated with vehicle died with typical neurological symptoms including hind limb weakness and paralysis.…”
Section: In Vivo Protection Of Mice From Lethal Challenge Of Zikvmentioning
confidence: 99%
“…For the viremia model in immunocompetent Balb/C mice [39,40], a group of 3-week-old female Balb/c mice infected intraperitoneally (ip) with 2 × 10 5 PFU of ZIKV strain GZ01/2016 were ip administered temoporfin at 0.02 mg/mice (n = 8) or vehicle control (n = 7) every day for 2 consecutive days post infection (dpi). Viremia on day 2 pi was determined by RT-qPCR, and statistical analysis was performed using the unpaired, two-tailed t-test.…”
Section: In Vivo Protection Efficacymentioning
confidence: 99%